Number of diaphyseal nutrient foramen on fully ossified dry left femur and their surgical importance - chowdhury, Md Shahajahan; Naushaba, Humaira; Begum, Jahanara; khan, Laila Farzana; Ara, Jubaida Gulshan; Parash, Tanvir Hossain (Journal of Dhaka National Medical College & Hospital, 2014)
Background : The femur is the strongest and longest bone of the human body which extends from the pelvis to the knee. It is the weight bearing typical long bone. The nutrient foramina are cavities that conduct the nutrient arteries. The majority blood supply for femur originates from the nutrient arteries, mainly during the growing period and during the early phase of ossification1. In bone grafts the nutrient blood supply is crucial and it should be preserved in order to promote the healing. Objective : The anatomy and number of nutrient foramen of femur is very essential for orthopedic & vascular surgeons as well as to radiologist for planning of treatment. This data could be useful as reference for surgical procedures of the lower limb. Material & Methods : This is a purposive sampling type of study carried out in the Department of Anatomy, Sir Salimullah Medical College (SSMC), Dhaka from July 2011 to June 2012. The study comprised 199 fully ossified left sided dry femur (n=89 male, n=110 female). The bones were collected from the Department of Anatomy, Sir Salimullah Medical College Dhaka. Morphometric study of nutrient foramen was carried out on all samples by direct physical and photographic methods. Result : The nutrient foramen were observed single in number in 84.36% male and 76.67% female samples, double in number in 13.28% male and 21.33% female samples and triple in number in 2.36% male and 2% female samples of left femur respectively. The anatomical knowledge about the study is useful in certain surgical procedures to preserve the circulation. As micro vascular bone transfer is becoming more popular, a convention for the anatomical description of nutrient foramen is important. J. Dhaka National Med. Coll. Hos. 2014; 20 (02): 40-42